A Review of Cytokines and Their Role in Inflammation - Sangary, Mohammad (Journal of Natural Sciences – Kabul University, 2021)
During the inflammatory process, several events occur, including capillary expansion, cell proliferation, differentiation, and the recruitment of immune system cells to the site of inflammation. But how do these events happen? Cytokines, which include chemokines, interferons, interleukins, lymphokines, tumor necrosis factor (TNF), colony-stimulating factors (CSF), and others, play a key role in these processes. These secretory materials induce or inhibit changes that develop during the inflammatory process. Cytokines bind to specific receptors on the surfaces of cells and are classified based on their functions in the immune system. They are produced by both immune and non-immune cells. Generally, pro-inflammatory cytokines play a significant role in initiating inflammation by causing capillary expansion, increasing permeability, and recruiting immune cells to the injury site. Conversely, anti-inflammatory cytokines inhibit most of these events to prevent excessive inflammation.